Village Economy Development through the National Program for Community Empowerment in Rural Areas (PNPM-MP) in Ngepung Village, Kedamean District, Gresik Regency - Siswanto; Wahyu Febriani; Priyo Utomo (Faculty of Economics Merdeka University Surabaya Jl. Ketintang Madya VII/2 Karah, Kec. Jambangan, Kota SBY, Jawa Timur 60232, 2019)
This study aims to find out villagers participation in supporting the success of the implementation of the National Program for Community Empowerment in Rural Areas (PNPM-MP) in the Ngepung Vilage, Kedamean District of Gresik. The research method used is qualitative research methods. The results show villagers participation in planning, in this case the community has played an active role, but has not been thoroughly to all the community, which in the process of meeting, not all people participate in meetings, in planning meetings represented by the Head of village, Chairman of RT and RW as well as community leaders , active in community planning in the making a decision, the goal of a series of activities, as well as to the determination of the funds that also involve all elements of society, including community leaders.Villagers Participation on Implementation of the Autonomy National People Empowerment Program (PNPM-MP) by the community through self-managed and facilitated by village and assisted by facilitators village that serves as a consultant PNPM. Carried out after the implementation phase of the planning phase is complete and has no funds allocation activities. people participation in the use and maintenance can be seen from the benefits perceived by people in the construction that has been done as well as improve the economy of society in physical form through road paving and toilet and empowerment of the women's credit form (SPP). In terms of physical development, people always have the initiative if there is damage occurred.